(untitled) (Research, Society and Development, 2021)
In this article, we present a qualitative documentary research entitled. “Ethics in basic education in the early grades with analysis of a paradidactic educational material”. Ethics in education involves certain difficulties in the performance of the teacher committed to student learning, and its definition is a set of principles that guide human relationships and guide decisions, overcoming the dilemmas found in the socio-moral environment. In this way, the child acquires experience in interpersonal relationships at school, developing morality, which allows us to discuss the importance of the role of ethics in schools, which helps in the construction of values in a society. In this context, the analysis of documents followed the contents of four categories; procedural, conceptual, attitudinal, factual that facilitates the teaching-learning process in its execution. In this perspective, this text helps in the continuing education of basic education teachers, with reflections on the role of teachers in the classroom.